Selective Radical Oxidation of Cyclohexane to Adipic Acid at Electrochemical Interfaces. Issue 2 (12th December 2022) - Tian, Hao; Zhang, Yujun; Zhang, Ziyang; Lv, Tingting; Bian, Lei; Wang, Hong; Li, Jianxin; Yamauchi, Yusuke; Wang, Zhong‐Li
Abstract: Direct conversion of cyclohexane to adipic acid (AA) under mild conditions is an attractive technology in response to the increasing industrial demand of chemical intermediate AA. Exploring advanced free radical oxidation systems is the key to converting cyclohexane in a direct and mild manner. This study demonstrates that electrocatalytic water oxidation can quantitatively generate hydroxyl radicals (⋅OH) to selectively oxidize cyclohexane to AA by a vanadium oxide (VOx )‐platinum (Pt) composite catalyst coupled with persulfate (PS) redox mediator at the electrode/electrolyte interface under ambient temperature and pressure. The three active components of VOx, Pt, and PS can produce different concentrations of ⋅OH radicals alone or in combination, resulting in different AA selectivity and cyclohexane conversion, and the activity increased with the increase of free radical concentration before AA peroxidation. The optimized ternary oxidation system of VOx ‐Pt‐PS achieved a cyclohexane conversion of 85 % with 95 % AA selectivity and the corresponding yield was 81 %, better than most traditional oxidation systems. Electrochemical interfaces‐driven radical oxidation provides opportunities to oxidatively convert many other inexpensive hydrocarbons to value‐added chemicals. Abstract : Direct conversion of cyclohexane to adipic acid (AA) with 85 % cyclohexane conversion and 95 % AA selectivity is achieved on electrochemical interfaces composed of vanadium oxide (VOx )‐platinum (Pt) catalyst and persulfate (PS) redox mediator.